THE DEVELOPMENT VILLAGE GOVERNMENT IN SYNERGITY OF THE IMPLEMENTATION IN LAW No. 6/2014 - Ibad, Syahrul (Universitas Muhammadiyah Jember, 2020)
This paper describes the development of village government in synergy of the implementation in law number 6/2014 using descriptive research method with a qualitative approach, the consistency of village development must be supported by commitment, awareness and active participation from all participant who interest in developing a village, as a case for realizing people welfare. In general, the success of village development will greatly depend on the ability of the supradesa government apparatus and the village government, as well as all the components (stakeholders) involved in the administration of the village administration, in understanding and utilizing the various potentials they have. The integrity of administration village governance can be realized through a planning execution of village Government by involving the community (according to local wisdom), the planning contains: 1) Legal and policy aspects that encourage the structuring of village community institutions in a sustainable governance development system; 2). Increasing community institutional participation aspects in making decision policy through a village government; 3). Institutional aspects, coordination and partnerships between community groups through an arrangement of village social institutions to increase community accessibility within technological innovation, credit, production facilities, and market information; 4). Supporting infrastructure aspects from the non-agricultural sector (market, irrigation, roads, electricity, etc.).